Analisis Pengembangan Ekspor Cengkeh Indonesia - Ely Nurhayati; Sri Hartoyo; Sri Mulatsih (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2018)
Exports are an important component of the economy. The higher export performance, the greater positive impact on the economy. From 2012 to 2016, Indonesia's exports continue to decline, so Indonesia needs to boost its exports again. One of the potential commodities developed is cloves. This study analyzes the development of Indonesian clove exports by finding out the competitiveness of cloves, as well as factors affecting its exports. The methods used are RCA, EPD, X-Model, and Gravity. The results of the analysis found that an optimistic market developed is Pakistan, Germany, Italy and United State of America. Potential markets to be developed are Malaysia, Vietnam, Thailand, France and Netherlands markets. Factors affecting Indonesian clove exports are GDP per capita, export price, economic distance and tariff. Keywords: Clove, EPD, Export, Gravity Model, RCA JEL Classification: C23, F10, F13